Kiai's Transformative Leadership in Developing an Organizational Culture of Islamic Boarding Schools: Multicase Study - Samsul Arifin; Moch. Chotib; Nurul Widyawati Islami Rahayu; Hosaini Hosaini; Wedi Samsudi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to analyze the transformative leadership of kiai in developing Islamic boarding school organizational culture. The research method used is qualitative with a case study approach. Data collection uses interviews, observation and documentation. Meanwhile, data analysis uses data reduction, data display, and conclusion/verification. The research results show that the leadership role of the Kiai in the Leadership Transformation is related to changes in roles and responsibilities within the Islamic boarding school and the ever-changing society while maintaining the organizational culture of the Islamic boarding school refers to efforts to maintain and develop existing traditions and distinctive identities. In the Islamic boarding school environment Transformative Kiai Leadership at that the Pondok Pesantren Al-Mashduqiah and the Pondok Pesantren Nurul Wafa Besuki, both Islamic boarding schools may stand out by having a clear and strong vision of the desired direction for the Islamic boarding school. This vision may not only be limited to the religious aspect, but also includes personal development, education, and social contribution. These kiai may convey collaborative leadership, and open communication, and be role models for the students in terms of integrity and Exemplary. This cultural development has had a positive impact on cultural development in the two Islamic boarding schools. Fostering a progressive educational culture, Islamic boarding schools become dynamic and relevant learning centers, preparing students to become skilled, knowledgeable individuals and contribute positively to society.